FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN USAHA MIKRO DI KOTA MEDAN - Raihanah Daulay (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2014)
Micro enterprise is a business that is run by individuals with limited capital and small-scale businesses, selling goods is limited to certain. Micro-businesses generate income Indonesia the third largest community, which shows micro businesses have to absorb the amount of labor that is high enough.But a lot of things that cause difficulty in the growth of micro-enterprises. The amount of competition that causes micro-enterprises are often under pressure so it is difficult to develop. This study aims to know the condition of micro enterprises that focuses on community-managed businesses and are in residential areas such as shops, kiosks and stalls. Seeing the condition of the existing micro-enterprises and the results can serve as guidelines to overcome the problems that occur so that micro businesses can grow and thrive. The using of research method is a survey research to know the condition and ability of micro-enterprises in developing the business and see what obstacles that hinder the development of micro-enterprises. The  research of population is micro businesses, such as shops, kiosks and shops belonging to people who are in residential areas in five subdistrict of Medan. Questionnaire, interview and observation data collection techniques are used. The research  of data were analyzed by using a single frequency tables and descriptive analysis.